2021
DOI: 10.2147/dmso.s301363
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Hyperuricemia and Metabolically Unhealthy Obesity: A Cross-Sectional Analysis in the Tianning Cohort

Abstract: Objective The relationship between obesity and hyperuricemia has been demonstrated by many studies. However, whether or to what extent metabolic condition influents the association between obesity and hyperuricemia was not clear. Here, we aimed to examine the association between obese-metabolic phenotype and hyperuricemia in a large sample of Chinese adults. Methods According to BMI and metabolic syndrome, obese-metabolic phenotype was defined as metabolically unhealthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
(52 reference statements)
3
9
0
4
Order By: Relevance
“…Previous studies have shown that obesity and its phenotypes are significantly associated with the risk of hyperuricemia, and the relationship are sex-specific and age-specific differences ( 29 31 ). In the Chinese population, Tian et al suggested that the MHOO phenotype was significantly associated with the risk of hyperuricemia only in women and not in men from the China Health and Nutrition Survey ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that obesity and its phenotypes are significantly associated with the risk of hyperuricemia, and the relationship are sex-specific and age-specific differences ( 29 31 ). In the Chinese population, Tian et al suggested that the MHOO phenotype was significantly associated with the risk of hyperuricemia only in women and not in men from the China Health and Nutrition Survey ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Chinese population, Tian et al suggested that the MHOO phenotype was significantly associated with the risk of hyperuricemia only in women and not in men from the China Health and Nutrition Survey ( 30 ). Yu et al found that MUOO, in comparison with MHOO, was significantly associated with hyperuricemia in Chinese adults ( 29 ). High serum UA levels have long been considered a potential master conductor in metabolic syndrome and fat storage ( 17 , 32 ), but it is still unknown whether serum UA is a risk factor of obesity-related metabolic phenotypes in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Other cross-sectional studies also indicated positive associations between BMI and HUA (30,31). BMI has been acknowledged to have a causal and independent effect on elevating the SUA level (5,30,32). However, BMI does not differentiate fat-free mass from adipose tissue (33) and may have a low sensitivity for predicting BFP (34).…”
Section: Discussionmentioning
confidence: 99%
“…In a large survey of 310,577 Japanese middle-aged adults, obese participants were found to have a 1.33-3.76-fold higher risk of HUA in comparison with their nonobese counterparts (29). Other cross-sectional studies also indicated positive associations between BMI and HUA (30,31). BMI has been acknowledged to have a causal and independent effect on elevating the SUA level (5,30,32).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is one of the major risk factors for HUA, and body mass index (BMI) was positively correlated with serum uric acid levels in previous studies (R = 0.96; p < 0.00001; Shirasawa et al, 2020;Yu et al, 2021). Tai et al (2020) has reported increased risk of gout when urate genetic risk scores are higher in low/normal-weight (OR: 2.89, 95% CI: 2.42-3.47), overweight (OR 3.09, 95% CI: 2.84-3.36), and obese individuals (OR 2.65, 95% CI: 2.46-2.86) based on BMI.…”
Section: Introductionmentioning
confidence: 95%